Membaca Ayat Poligami Dalam Kerangka Penafsiran Kontekstual Abdullah Saeed: Studi QS an-Nisa’ ayat 3 - Dhulkifli, Muhammad Luthfi (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
This article discusses polygamy verse on contextual approach’s Abdullah Saeed. This approach will argue whether polygamy is permitted or prohibited on Abdullah Saeed’s thought. Polygamy is a condition which the husband who have more than one wife together in the same situation. It is a classical and everlasting problems because there are many contradiction in Muslim realm. Abdullah Saeed haven’t been giving a comprehensive exegesis in his work about it, so it will be new research approach. In the other hand, Abdullah Saeed’s contextual approach will give deeply interpretation towards polygamy verse in our life today. This research is library research with descriptive-analytic method to discover the verse in Abdullah Saeed’s approach.